Biological aspects of Schilbe intermedius (Ruppell, 1832) in the Nyanza Gulf of Lake Victoria, Kenya. Issue 1 (26th January 2020) - Mutethya, Eunice; Okoth, Sharon; Yongo, Edwine
Abstract: Silver butter catfish ( Schilbe intermedius ) is an indigenous fish species in Lake Victoria. It has a good economic value because of the quality and freshness of its flesh, increasing its demand for consumption. It is potamodromous, with its stock in the lake declining because of overexploitation by the use of illegal fishing gears at the river mouths on their way to spawning areas. Fish samples (321) were obtained from commercial gill net (1.5–3 in.) fishers within Nyanza gulf. The fish samples were weighed (g) and measured (cm), dissected and sex determined by visual inspection of the gonads. Ovaries for mature female fish specimens were preserved for analysis of fecundity. Fecundity was determined by the gravimetric technique. The mean (± SE ) length and weight for all fish were 18.2 ± 0.2 cm TL and 51.9 ± 1.9 g, respectively. The female fish (20.0 ± 0.2 cm) were significantly ( F = 199.80, p < .05) larger than the males (15.9 ± 0.1 cm). Similarly, the females (68.8 ± 2.6 g) were significantly ( F = 152.61, p < .05) heavier than the males (30.93 ± 1.02 g). The overall sex ratio was 1.23:1.0 (female:male). The length frequency exhibited a unimodal distribution, with the modal class between 16 and 18 cm for either sex. The regression slope ( b ) of the length–weight relationship was 3.2, 3.1 and 3.0 for all fish, females and males. The absolute fecundity ranged from 6, 510 to 59, 818 eggs, with a mean of 34, 473 eggs. The length at 50% maturity was estimated to be 16.0 cm (female) and 18.0 cm (male) fish. The mean length and size at maturity of S. intermedius have declined, likely attributable to fishing effects, changes in food resources, competition and predation. Thus, the present study provided relevant biological data of S. intermedius, which is currently limited for this region.